Insert injection molding of low-density polyethylene single-polymer composites reinforced with ultrahigh-molecular-weight polyethylene fabric. (August 2018) - Wang, Jian; Chen, Dongjie; Wang, Sui; Du, Ziran; Jiang, Nannan; Peng, Jiong
Low-density polyethylene single-polymer composites (SPCs) reinforced with sandwiched ultrahigh-molecular-weight polyethylene woven fabric were prepared by insert injection molding. The process combines aesthetic and processing advantages. A processing temperature window (135–155°C) of a very short cycle time (less than 30 s) could be realized. The mechanical properties and morphologies of the samples were evaluated. The results suggested that the polyethylene SPCs were prepared successfully with concurrent increases in flexural strength (∼57%), tensile strength (∼164%), and impact strength (∼69%). The effects of different processing parameters including the nozzle temperature, injection pressure, injection speed, and the holding time were discussed. Numerical simulation results were used in the analysis.